A new application for the concept of pedagogical content knowledge: teaching advanced social science research methods. (3rd March 2020) - Nind, Melanie
ABSTRACT: This paper takes the concept of pedagogical content knowledge (PCK), which is well known in teacher education, and applies it in research methods education where it has not been previously used. It asks how experienced social science research methods teachers, who know their subject (method) well, teach advanced social research methods to others. Drawing on a wider, multi-method qualitative study conducted in the UK, the paper shows the participating teachers' orientation to teaching methods and how they combine knowledge of content and pedagogy in generic and distinctive PCK. It shows specifically their use of data for translating methods to become readily knowable for students. The case is made for identifying PCK through dialogic means as a vehicle for stimulating attention to the pedagogical dimension within policy-critical efforts to build research capacity.